2011
DOI: 10.1177/0027950111420917
|View full text |Cite
|
Sign up to set email alerts
|

Received Wisdom and Beyond: Lessons from Fiscal Consolidation in the EU

Abstract: Restoring sustainable public finances in the aftermath of the Great Recession is a key challenge in most EU countries. In order to learn from history, our paper examines consolidation episodes in the EU since 1970. We shed light on the factors that favour the start of a consolidation episode and determine its success. Compared to the existing literature, we add a number of new dimensions in the analysis. First, we explore a broader set of potential ingredients of the 'recipe for success', including the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 22 publications
0
61
0
1
Order By: Relevance
“…As a general rule, fiscal consolidation is undertaken only when public finances are weak, as measured by rising deficits and debt levels (Molnar ). In fact, some studies suggest that the gravity of the initial fiscal conditions influences nations to undertake deeper and more prolonged consolidations, which have a greater chance of stabilizing debt in the future (Larch and Turrini ; Perotti ).…”
Section: Achieving the Politically Improbablementioning
confidence: 99%
See 1 more Smart Citation
“…As a general rule, fiscal consolidation is undertaken only when public finances are weak, as measured by rising deficits and debt levels (Molnar ). In fact, some studies suggest that the gravity of the initial fiscal conditions influences nations to undertake deeper and more prolonged consolidations, which have a greater chance of stabilizing debt in the future (Larch and Turrini ; Perotti ).…”
Section: Achieving the Politically Improbablementioning
confidence: 99%
“…This included the shadow cast by the original economic and fiscal crisis of the mid‐1980s and the reliance of the Australian economy on foreign sources of capital to finance private investment. Today, as national leaders engage in yet a new round of consolidation to bring modest deficits into surpluses, one observer concluded that budget surpluses have come to serve as a symbolic metaphor for the competence of the government—the single most important “acid test” of a government's economic credentials (Hawke and Wanna ).…”
Section: Achieving the Politically Improbablementioning
confidence: 99%
“…Cohesive single parties controlling government are more likely to develop and successfully achieve fiscal consolidation packages than fragmented coalitions. Coalition partners often have difficulty agreeing on packages compared to more unified parties (Larch and Turrini 2008). Since proportional representation systems tend to foster politically fragmented regimes, some have generalized that governments with majoritiarian electoral systems maintain tighter fiscal discipline than other systems (Persson and Tabellini 2003).…”
Section: Understanding the Politics Of Fiscal Austeritymentioning
confidence: 99%
“…Evidence from the 1970s and 1980s suggested that fiscal consolidation on the scale we discuss was better done by cutting spending. Larch and Turrini (2008) look at more recent efforts, and suggest that this result reflected picking the low hanging fruit, and that a more balanced approach based on a strong fiscal framework would now be more appropriate.Given the increased debt stock, there is continual worry about the possibility that a risk premium will arise on UK government debt, and on UK debt in general, and that these would have a deleterious effect on prospects for the economy. If such a premium arises, then government interest payments and hence tax rates (or borrowing) will have to be higher.…”
mentioning
confidence: 99%
“…Evidence from the 1970s and 1980s suggested that fiscal consolidation on the scale we discuss was better done by cutting spending. Larch and Turrini (2008) look at more recent efforts, and suggest that this result reflected picking the low hanging fruit, and that a more balanced approach based on a strong fiscal framework would now be more appropriate.…”
mentioning
confidence: 99%